2008
DOI: 10.1007/s12253-008-9131-z
|View full text |Cite
|
Sign up to set email alerts
|

CD147 Expression Indicates Unfavourable Prognosis in Prostate Cancer

Abstract: Extracellular matrix metalloproteinase inducer (EMMPRIN, also named as CD147) is a multifunctional membrane glycoprotein over-expressed in many kinds of human solid tumors. It has been demonstrated to be involved in tumor invasion and angiogenesis. The aim of this study was to analyze the clinicopathological characteristics of the expression of CD147 in human prostate cancer (PCa), and to evaluate its clinical significance in the histologic classification and prognosis of PCa. CD147 protein expression in paraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
31
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 29 publications
7
31
0
Order By: Relevance
“…Diagnosis and treatment of PCa has had many advances in the past 20 years; unfortunately, the existing treatment approaches and surgical interventions have been proven to be inadequate for the management of this disease (1,2). PCa deaths are a result of metastatic disease and treatment of such metastatic disease is one of the major therapeutic challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis and treatment of PCa has had many advances in the past 20 years; unfortunately, the existing treatment approaches and surgical interventions have been proven to be inadequate for the management of this disease (1,2). PCa deaths are a result of metastatic disease and treatment of such metastatic disease is one of the major therapeutic challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Especially in PCa, Wang et al (20) found that CD147 downregulation by RNAi technology could decrease the invasive capability of the PCa cells; data of our research group (21) and Madigan et al (22) both showed that CD147 could regulate MMPs and was involved in PCa progression. Hao et al (23) also reported that CD147 expression may be correlated with drug resistance during PCa metastasis and may be a useful potential therapeutic target in advanced disease; our research group further identified the potential role of CD147 as an independent predictor of biochemical recurrence, development of metastasis and reduced overall survival in PCa (24,25). However, the mechanisms that result in the aberrant expression of CD147 in PCa are not fully elucidated.…”
Section: Introductionmentioning
confidence: 61%
“…Previous studies have shown that EMMPRIN/CD147, through multiple pathways and mechanisms, stimulates adjacent fibroblasts to produce matrix metalloproteinases, and thus promotes survival, invasion and metastasis of tumor cells (13,(18)(19)(20)(21)(22)(23)36). Indeed, EMMPRIN/CD147 expression is correlated significantly with the stage of clinicopathology in thyroid carcinoma (9), adenocarcinomas (7), esophageal squamous cell carcinomas (37) and prostate cancer (14). Furthermore, treatment with anti-EMMPRIN/CD147 antibody delays the formation of tumors in animal models (38).…”
Section: Discussionmentioning
confidence: 98%
“…EMMPRIN/CD147 is a highly glycosylated transmembrane protein belonging to the immunoglobulin superfamily 34 and is widely presented and/or overexpressed on the membrane surface of various malignant tumor cells (7,8,(10)(11)(12)(13)(14)(15)(16)(17). Due to its close association with pathological classification and overall survival analysis, EMMPRIN/CD147 has been potentially suggested as a prognostic factor in certain types of malignant tumors (7,8,10,(12)(13)(14)(15)17,(21)(22)(23)(24). In the present study, our results indicated that EMMPRIN/CD147 was expressed not only in all three human osteosarcoma cell lines, but also in the cell membrance and cytoplasm of osteosarcoma tissues from the majority of patients pathologically diagnosed with osteosarcoma at grade IIA or above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation